Indirect Compensation dan Work Environment Terhadap Employee Performance (Studi pada PKS AEK TOROP di Labuhanbatu Selatan) - Utama Rambe, Suma Budi; Sihombing, Marlon; Siregar, Onan Marakali (Universitas Serambi Mekkah, 2024)
In today's industrial development, human resources are very important for every company institution to realize the vision and mission determined by the company organization. Although there are still many other factors that can help realize the company's vision and mission, without the support of human resources, the company's operations will not function properly. This shows that human resources are the main key that must be considered with all its needs. The objectives of this study are 1) To find out how much influence indirect compensation has on employee performance, 2) To find out how much influence the work environment has on employee performance, 3) To find out how much influence indirect compensation and work environment have on employee performance. This study uses a quantitative research method with an associative approach. The method of data collection is distributing questionnaires. The number of samples studied was 60 people. The methods used in this study are instrument testing, classical assumption testing, multiple linear regression testing, and hypothesis testing. The results of this study indicate that indirect compensation (X1) has a significant effect on employee performance (Y) as evidenced by the results of Tcount (2.532) Ttable (1.672). Work environment (X2) has a significant effect on employee performance (Y) as evidenced by the results of Tcount (2.563) Ttable (1.672). Indirect compensation (X1) and work environment (X2) together have a positive and significant effect on employee performance (Y) as evidenced by the results of the simultaneous significance test Fcount (6.924) Ftable (3.16). In the calculation of the coefficient of determination, the result is 0.195, which means that the independent variable affects the dependent variable by 19.5%, while the remaining 80.5% is influenced by other variables.